2000
DOI: 10.1021/ie000124k
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Nickel-Based Alloys in Supercritical Water Oxidation Systems

Abstract: There is a need to destroy both military and civilian hazardous waste and an urgency, mandated by public concern over traditional waste handling methodologies, to identify safe and efficient alternative technologies. One very effective process for the destruction of such waste is supercritical water oxidation (SCWO). By capitalizing on the properties of water above its critical point (374 °C and 22.4 MPa for pure water), this technology provides rapid and complete oxidation with high destruction efficiencies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Iron based alloys showed a weaker corrosion resistance than nickel based alloys in previous SCWO corrosion studies, especially in the chlorinated solution (38). The 316L alloys showed the highest corrosion rate about 50 mmyr -1 among all alloys, indicating austenitic stainless steel was not suitable for chlorinated feed in SCWO (29). When the test of decomposing organic matter was conducted, it was always found that the carboncontaminated covered the surface of alloys due to the incomplete degradation of organic matter (26,28).…”
Section: Corrosion Results Of Candidate Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Iron based alloys showed a weaker corrosion resistance than nickel based alloys in previous SCWO corrosion studies, especially in the chlorinated solution (38). The 316L alloys showed the highest corrosion rate about 50 mmyr -1 among all alloys, indicating austenitic stainless steel was not suitable for chlorinated feed in SCWO (29). When the test of decomposing organic matter was conducted, it was always found that the carboncontaminated covered the surface of alloys due to the incomplete degradation of organic matter (26,28).…”
Section: Corrosion Results Of Candidate Materialsmentioning
confidence: 99%
“…It is known that the high temperature subcritical water has higher corrosive and solubility than supercritical water. Alloys always get a higher corrosion rate at subcritical condition than supercritical condition and the higher destruction efficiency of organic matter at subcritical condition because of the more dissolved catalytic alloying elements by severe corrosion (16,29,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The high pressure 60 MPa could cause intergranular corrosion and higher corrosion rate than 25 MPa by more than two orders of magnitude, indicating the importance of density of water on corrosion behavior of alloys (49).…”
Section: Corrosion Results Of Candidate Materialsmentioning
confidence: 99%
See 3 more Smart Citations